Generation Y workplace needs and preferred leadership at Telekom Malaysia / Nurul‘ Izzah Mohd Sanusi - Mohd Sanusi, Nurul ‘ Izzah (Faculty of Business and Management, 2015)
The recruitment of Generation Y of the individuals that were born between the year 1980-2000 are increasing in the workplace at Telekom Malaysia making it imperative for the employers or managers to understand their needs to retain them working effectively for the company. Although there are many Gen Y characteristics and needs that are published in the existing literature, the researcher believe that the most preferred leadership is still not clear among this generation that can actually support their workplace needs. This study aims to answer two-research question: What are the Gen Y needs in the Workplace at Telekom Malaysia and what type of leadership best supports these needs at Telekom Malaysia. The researcher had distributed the survey that was emailed to 110 employees of Gen Y’s at Telekom Malaysia Perak Branch. Out of the 110, 103 online surveys were completed. Communication was found to be the highest priority needs, followed by flexibility, technology, teamwork and challenging work that was also considered high priority towards the Gen Y’s at Telekom Malaysia. The researcher found that Gen Y’S at Telekom Malaysia have high preferences to work with a leader that implemented Participative Leadership and Transformational. From the final results, all of the objectives are achieved and a positive feedback was given from the respondents.